2018
DOI: 10.14710/jkli.17.2.95-103
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Spasial dan Temporal Persebaran Kasus Baru TB Paru BTA (+) di Kabupaten Batang

Abstract: Latar belakang: Case Notification Rate (CNR) Kabupaten Batang tahun 2013 sebesar 73,8/100.000 penduduk. Berdasarkan CNR-nya Kabupaten Batang masuk peringkat ke-9 dari 35 kabupaten/kota di Jawa Tengah. Selain itu, pada tahun 2012-2014 tren kasus baru TB paru BTA positif selalu menurun, kemudian meningkat tahun 2015, dan turun kembali di tahun 2016. Namun, tren tersebut tidak menggambarkan tren kasus baru di tiap kecamatan yang ada di Kabupaten Batang. Tujuan dari penelitian ini adalah untuk mengetahui gambaran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…Tuberculosis is a disease that is transmitted from one person to another through the air. High population density increases the opportunities for interaction or contact between people that increase the transmission of disease (Siwiendrayanti, Sukendra, & Arofah, 2018). The result of this study is in line with the research conducted in Lampung Province which stated that the population density of an area, spatially, was one of the risk factors of tuberculosis, when the population density increased by 1000 population per km2, the number of cases would increase by 11.78 cases (Rosari, Bakri, Santoso, & Wardani, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is a disease that is transmitted from one person to another through the air. High population density increases the opportunities for interaction or contact between people that increase the transmission of disease (Siwiendrayanti, Sukendra, & Arofah, 2018). The result of this study is in line with the research conducted in Lampung Province which stated that the population density of an area, spatially, was one of the risk factors of tuberculosis, when the population density increased by 1000 population per km2, the number of cases would increase by 11.78 cases (Rosari, Bakri, Santoso, & Wardani, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The spread of new cases of Tb did not show a pattern of spread following the cure rate pattern and almost entirely following the pattern of distribution of healthy home coverage. Even the change in risk of Tb cluster was linked to socioeconomic and patient care factors [25], [26]. The results showed that several risk factors for the incidence of Tb were related to income levels, lighting, humidity, floor conditions, and ventilation (Table 2).…”
Section: Risk Factors For Tb Incidencementioning
confidence: 97%
“…7 Beberapa faktor yang menyebabkan penyebaran TB yaitu kepadatan penduduk, kondisi ekonomi rumah tangga, pelayanan kesehatan yang tersedia dan dapat diakses, sanitasi rumah tangga dan kebiasaan perilaku PHBS. 9 Strategi pencegahan TB yang efektif yaitu dengan diagnosis dini dan pengobatan yang tepat yang dapat dilaksanakan jika fasilitas kesehatan mudah diakses dan siap menawarkan layanan TB. [10][11][12][13] Sebagian besar negara berkembang masih sulit menjangkau akses dan kualitas layanan kesehatan, fasilitas yang tidak lengkap dan tidak menggunakan teknologi diagnostik canggih dalam sistem kesehatan karena kemiskinan yang berkelanjutan.…”
Section: Pendahuluanunclassified